2018
DOI: 10.2196/jmir.8630
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a Web-Based Social Anxiety Intervention Among University Students: Randomized Controlled Trial

Abstract: BackgroundTreatment rates for social anxiety, a prevalent and potentially debilitating condition, remain among the lowest of all major mental disorders today. Although computer-delivered interventions are well poised to surmount key barriers to the treatment of social anxiety, most are only marginally effective when delivered as stand-alone treatments. A new, Web-based cognitive behavioral therapy (CBT) intervention called Overcome Social Anxiety was recently created to address the limitations of prior compute… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 38 publications
(48 reference statements)
2
37
0
1
Order By: Relevance
“…A small pilot study ( N = 38) on therapist guided self‐help found comparable effects for changes in SAD on the SPS ( d = 1.18 vs. 1.14 in the present study) but somewhat smaller effects with regard to changes on the SIAS ( d = 0.81 vs. d = 1.17 in the present study; Tillfors et al, ). Recently, McCall et al () reported somewhat smaller within‐group changes for unguided self‐help in a non‐clinical student sample with SAD symptoms (SIAS: d = 0.72), where between‐group effects were comparable with the present study ( d = 0.56). However, the authors reported completer data only, and the dropout rate in the study was substantial (>35%).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A small pilot study ( N = 38) on therapist guided self‐help found comparable effects for changes in SAD on the SPS ( d = 1.18 vs. 1.14 in the present study) but somewhat smaller effects with regard to changes on the SIAS ( d = 0.81 vs. d = 1.17 in the present study; Tillfors et al, ). Recently, McCall et al () reported somewhat smaller within‐group changes for unguided self‐help in a non‐clinical student sample with SAD symptoms (SIAS: d = 0.72), where between‐group effects were comparable with the present study ( d = 0.56). However, the authors reported completer data only, and the dropout rate in the study was substantial (>35%).…”
Section: Discussionsupporting
confidence: 81%
“…A small open trial ( n = 38) that delivered PDFs with self‐help material and offered minimal contact with a psychotherapist resulted in large pre–post within‐group effects (Social Interaction Anxiety Scale [SIAS]: d = 0.81; Social Phobia Scale [SPS]: d = 1.18) for both the iCBT group and the iCBT group with additional in vivo group exposure (Tillfors et al, ). Another unguided web‐based intervention that was personalized to each user's symptoms yielded smaller pre–post effect sizes in a non‐clinical sample of psychology students (e.g., SIAS: d = 0.72; McCall, Richardson, Helgadottir, & Chen, ).…”
Section: Introductionmentioning
confidence: 99%
“…In 14 studies, participants were guided through the intervention by a therapist or researcher. The other 10 interventions were self-guided (ie, unguided) [ 58 , 59 , 65 - 72 ]. Guidance was provided through telephone and/or email contact [ 63 , 64 , 73 - 78 ], chat sessions [ 79 ], or face-to-face guidance during the participant’s completion of the modules [ 60 - 62 , 80 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…With 1 app for patients suffering from suicidal thoughts, more subjects reported suicidal ideation using the app than they did on the traditionally administered Patient Health Questionnaire (PHQ-9) [9]. Psychological artificial intelligence (AI) delivering cognitive behavioral therapy (CBT) has been shown to be a feasible, engaging, and effective solution for reducing symptoms of depression and anxiety in college students [10-12]. However, the efficacy of using psychological AI to deliver integrative mental health care, including CBT, requires further exploration.…”
Section: Introductionmentioning
confidence: 99%